Editing the Arabic Manuscript - Grammar and Stages - hrouz, abdelghani; betta, merzoug (Journal of Social Sciences and Humanities, 2021)
In recent years, the world has witnessed a great interest in manuscripts, including the Islamic and Arab world, and despite the disasters, tribulations and conflicts it is going through in various political and economic fields, this did not negate the great interest in manuscripts from various manuscript centers and university libraries, as well as researchers and others. The observer of the state of libraries in the world finds that the printed book is developing, and the increase in demand for it is caused by technology and scientific development in this field, as well as the emergence of electronic printing on various digital vessels, but interest in the manuscript, its achievement and preservation is increasing day by day due to its technical and aesthetic characteristics. Which distinguishes it from other office vessels, in addition to its cultural, scientific and historical value. Therefore, the researcher aims, behind the investigation of ancient manuscripts, to publish a correct and verified text of the historical document, and there are special rules and methods for achieving and publishing manuscripts agreed upon by most researchers, and given the importance of publishing Arabic manuscripts that include Arab heritage in various fields of knowledge, we find it necessary to address the most important methods And the methods used in achieving Arabic manuscripts. In order to achieve the manuscript and facilitate its use, researchers strive to achieve this purpose, by holding scientific forums and urging official bodies to establish centers for manuscripts and their implementation, and to encourage students to study and achieve heritage. But it is noticed on the ground that the lack of experience and attempts related to the process of verifying manuscripts makes the process not easy, given that the investigation of these manuscripts passes through scientific stages and systematic methods that follow their investigator's approach that only specialists in the field of investigation know. As a result of this, the basic problem that this article revolves around is: What are the scientific rules and stages that the investigator follows in the investigation process?